Non-similar analysis of radially magnetized flow and heat transfer of Reiner–Philippoff based nanofluid over a curved stretching surface with viscous dissipation - Jan, Ahmed; Nawaz, Rab; Ahmad, Adeel (International Journal of Thermofluids, 2024)
The aim of this study is to conduct a non-similar analysis of flow and heat transfer rheology of non-Newtonian fluid over a radially magnetized curved stretching surface in the presence of multiple type of nanoparticles. Reiner–Philippoff viscosity and homogenous models are incorporated in the governing equation to study the effects of non-Newtonian fluid and nanoparticles respectively. Reiner–Philippoff viscosity model is a complicated non-Newtonian fluid model presenting an implicit stress-strain relationship. This fluid model has ability to present viscosity behavior in response to varying viscoelastic conditions of shear-thinning, shear-thickening as well as Newtonian fluid. The nanoparticles of nickel, molybdenum disulfide, and tantalum are used to study the enhancement of the thermal conductivity of the fluid with influences of radiative heat flux and viscous dissipation. To attain a more precise and generalized analysis of the heat transfer and flow, the governing boundary layer equations are converted to non-similar form. The local non-similarity method up to second level of truncation is employed to numerically solve the resulting non-similar PDEs via bvp4c in MATLAB tools. To examine the impact of physical factors on flow and heat transfer, numerical data are visually and tabulated displayed. It is worth mentioning that the thermal radiation, curvature parameter, and magnetic number play important role in controlling wall drag and heat flux.